Analisis Efektivitas Mesin CNC Turning Goodway GCL-2BL pada Departemen Machining Perusahaan Foundry Menggunakan Metode TEEP - Yovindra Anggita Dyah Fortuna; Bayu Wiro Karuniawan; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Goodway CNC turning machine GCL-2BL number T6 is one of 5 Goodway GCL-2BL CNC turning machines in the machining department of a foundry company. The machine works continuously for 24 hours in three shifts per day. In the production period from March 2022 to February 2023, the machine produced as many as 27 types of products. Machines that work continuously beyond normal limits can reduce machine capabilities, production capacity and speed up the replacement of machine spare parts due to damage that occurs to the machine. Therefore, measuring the effectiveness of the machine needs to be done to find out how the condition of the machines and equipment in the company. The method used to measure machine effectiveness is the Total Effective Equipment Performance (TEEP). In addition to TEEP, this study used FMEA and FTA methods to analyze the factors causing the low level of effectiveness of the machine. Based on the results of the data processing that has been carried out, the TEEP value is 32.43%. This value is still far below the TEEP global standard of 80%. The most influential factor that influenced the low value of TEEP was the availability rate. Based on FMEA and FTA analysis, 21 problems caused low availability rate values and 27 alternative corrective solutions were found to overcome the problems. One of the problems found was leakage of pump oil and turret hydraulic oil. This factor is caused by the long service life and quality of the seal, which is less durable, so an alternative solution to overcome the problem is to replace the seal component with a new one.